Audit Evaluasi Sistem Manual Peminjaman Alat Praktikum Dengan Framework Cobit 5 - Amani Khansa, Setia; Magdalena, Hilyah (METIK JURNAL (AKREDITASI SINTA 3), 2025)
SMK Negeri 1 Simpang Katis is a vocational school focused on industrial mechanics education with various majors such as industrial vehicle engineering, motorcycle business and engineering, multimedia, software engineering, and electrical power installation engineering. Currently, the practical equipment loan system is still manual, often resulting in unorganized records, data loss, and difficulties in monitoring equipment usage. An audit using the COBIT 5 framework could help identify weaknesses in the current system and provide recommendations for improvement. By implementing a more structured approach to equipment management, the school can enhance accountability, streamline operations, and ultimately better support its students' hands-on learning experiences. f Furthermore, investing in a digital management system could facilitate real-time tracking of equipment loans, ensuring that all transactions are accurately recorded and easily accessible. This transition simplifies the auditing process and fosters a culture of responsibility among students and staff, leading to more effective utilization of resources. The framework indicates that all analyzed subdomains are still at Level 1 (Performed Process), while the expected target is Level 3 (Established Process). This means the system is operational but not yet well-documented or standardized. This study employs a gap analysis method by comparing the current condition with the desired target. The results reveal a significant gap in several subdomains, with an average score ranging from 1.5 to 2.5. Subdomains with the lowest scores, such as BAI02 (1.8) and BAI05 (1.9), highlight the need for better planning and system implementation. Therefore, this study recommends digitalizing the loan system, standardizing procedures through SOP development, enhancing control mechanisms, and providing user training to make the system more efficient, transparent, and well-documented.